2012
DOI: 10.1177/0022343312436768
|View full text |Cite
|
Sign up to set email alerts
|

Does transnational terrorism reduce foreign direct investment? Business-related versus non-business-related terrorism

Abstract: Although several existing studies examine the economic impact of transnational terrorism by referring to its potential to reduce foreign direct investment (FDI), they overlook possible differences in the effects of business-related and non-business-related terrorism. We argue that the former type of terror negatively affects FDI since it damages multinationals' buildings, destroys their products, kills their employees, and causes a rise in insurance premiums. The latter type of terror, however, does not induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 40 publications
(56 reference statements)
1
35
4
Order By: Relevance
“…The findings contradict those of Estrada et al (), Halkos et al (), and Maitah et al (), who find a positive relationship between GDP per capita and terrorism. Moreover, unlike Powers and Choi (), the study finds that FDI has a negative and significant impact on terrorism.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The findings contradict those of Estrada et al (), Halkos et al (), and Maitah et al (), who find a positive relationship between GDP per capita and terrorism. Moreover, unlike Powers and Choi (), the study finds that FDI has a negative and significant impact on terrorism.…”
Section: Discussioncontrasting
confidence: 81%
“…The northern half of the Tunisian–Algerian border has become a prime area for the circulation of cannabis resin. Finally, it is found that there is a negative and significant relationship between FDI and terrorism (Powers & Choi, ). An increase in 1% in the level of FDI generates a reduction of .21% in the number of terrorist attacks.…”
Section: Resultsmentioning
confidence: 99%
“…PolV data is from the ITERATE covering 1995-2012 and 2013-2016, and that of the Armed Conflicts provided by the Uppsala conflict data program (UCDP) compared and used. These were used in the past to assess PolV (Li, 2006;Powers & Choi, 2012). The variable DNC is proxied by external conflict involving conflicts across Nigerian borders on both the northern and southern borders.…”
Section: Methodsmentioning
confidence: 99%
“…Country-level research includes whether country stability and economic growth exert a dampening effect on terrorism (Choi, 2015) and whether terrorism reduces foreign direct investment as a consequence of damage to MNCs' buildings, stock, potential death of employees and ever-increasing insurance premiums (Powers & Choi, 2012). Terrorism is frequently perceived as a type of political risk (Saha & Yap, 2014) and therefore may deter foreign investors by creating awareness of an unsafe investment environment.…”
Section: Country-level Perspectivementioning
confidence: 99%